Increasing Management Relevance and Competitiveness : Proceedings of the 2nd Global Conference on Business, Management and Entrepreneurship (GC-BME 2017), August 9, 2017, Universitas Airlangga, Surabaya, Indonesia - Sukoco, Badri Munir (Boca Raton, FL : CRC Press, 2018)
"Increasing Management Relevance and Competitiveness contains the papers presented at the Global Conference on Business, Management and Entrepreneurship (the 2nd GC-BME 2017), Surabaya, Indonesia on the 9th of August, 2017.The book covers 7 topics:1. Organizational Behavior, Leadership, and Human Resources Management2. Innovation, Operations and Supply Chain Management3. Marketing Management4. Financial Management and Accounting5. Strategic Management, Entrepreneurship, and Contemporary Issues6. Green Business7. Management and Economics Education"--Provided by publisher.
Includes bibliographical references and index.
Also available in print format.
Keywords: Business, Management and Accounting; BUSINESSnetBASE/MANAGEMENTnetBASE; INFORMATIONSCIENCEnetBASE; Small Business Management; Strategic Management; Electronic books